Accumulation of heavy metals in the physical and biological systems of Lake Koka, Ethiopia: Implications for potential health risks. Issue 3 (26th August 2020) - Tessema, Kassahun; Lemma, Brook; Fetahi, Tadesse; Kebede, Elizabeth
Abstract: Lake Koka has several important socioeconomic uses, hydroelectric power generation, domestic water supply, irrigation, recreation and fishery. It is currently under serious threat, however, because of point and nonpoint pollution inputs. The objective of the present study was to examine the concentration of heavy metals (Mn, Cr, Pb, Zn, Cu, Ni and Cd) and their bioaccumulation, and biomagnification factors along the lake's food chain in order to assess the potential human and ecological health risks. Water, sediment and plankton samples were collected from seven sampling sites and fishes were purchased on site from fishers. The analyses were performed using a graphite furnance atomic absorption spectrophotometer. Heavy metals levels in the sediment samples were ranked in the order of Mn > Cr > Pb > Zn > Cu > Ni > Cd. Similarly, the metal concentration in the fish muscles was Cr > Cu > Pb > Cd. The sediment bioaccumulation factor (<1) and water bioaccumulation factor (>1) for Cd, Pb and Cr indicated the lake water exhibited higher concentrations than the sediment. In parallel, the Cr biomagnification factor for zooplankton, catfish, Nile tilapia and common carp was 1.63, 1.18, 1.36 and 2.28, respectively. The Cr concentrations at the Modjo (or Mojo) Upstream, Modjo Downstream and Kentare sites, and the Pb concentrations at riverine sites were above the permissible limits established by the World Health Organization. Cr ranked as fish species > zooplankton > phytoplankton, being above the permissible limits in catfish, Nile tilapia and common carp. Generally, the weekly intake estimates were considerably lower than the tolerable human intake values provided by WHO and others. However, Cr biomagnified along the trophic levels ultimately reaching the top consumers, with Cr (VI) being carcinogenic. The lake is a major fishery source, indicating care must be taken in regard to the weekly intake of the fishes, particularly common carp.